Von Meyenburg complex clinically presenting as metastatic liver nodule: A rare finding in an elderly male - Shirazi, Nadia (J Lab Physicians, 2019)
Von Meyenburg complex is a benign biliary hamartoma observed in approximately 3% of the autopsies conducted. These hamartomas are small, multiple and can be seen anywhere in the liver. There is usually no abnormality in liver function tests, and the patient is mostly asymptomatic. They serve as a diagnostic dilemma, particularly during metastatic workup in suspected cancer patients. Imaging studies are usually noncontributory, and biopsy is necessary for a definite diagnosis. We present here a middle-aged North Indian male who underwent liver biopsy to rule out metastasis.